Inactivation of Salmonella Enteritidis and Enterococcus faecium NRRL B-2354 in corn flour by radio frequency heating with subsequent freezing. (August 2019) - Ozturk, Samet; Liu, Shuxiang; Xu, Jie; Tang, Juming; Chen, Jinru; Singh, Rakesh K.; Kong, Fanbin
Abstract: This study aimed to evaluate the feasibility of using Enterococcus faecium NRRL B-2354 ( E . faecium ) as a surrogate of Salmonella enterica Enteritidis PT30 ( S . Enteritidis PT30), validate radio frequency (RF) heating in pasteurizing corn flour, and study the effect of subsequent freezing treatment after RF heating in enhancing the microbial inactivation effect. Corn flour with water activity of 0.45 ± 0.05 at 25 °C was homogeneously inoculated with S . Enteritidis PT30 and E. faecium separately at 8.50 ± 0.23 log CFU/g. Thermal resistance parameters in corn flour were determined in a water bath at 75, 80, and 85 °C and RF heating was used to pasteurize 3.18 kg corn flour with subsequent freezing storage at −20 °C. Results showed that the thermal resistance of E . faecium was higher than S . Enteritidis PT30. Samples heated to 85 °C, held for 10 min after heating in a RF system, and then stored at −20 °C for 48 h, resulted in the reduction of S . Enteritidis PT30 by 6.59 ± 0.21 log and E . faecium by 4.79 ± 0.17 log. E . faecium could be used as its surrogate for validation studies in the packaged corn flour. Results also confirmed that RF heating combined with freezing storage treatment could significantly reduce the survival of both microorganisms in corn flour. Highlights: Enterococcus faecium is a valid Salmonella surrogate in corn flour. An inoculated pack procedure to validate radio frequency pasteurization of corn flour was developed. Inactivation kinetics of both Salmonella and surrogate were determined at 75, 80 and 85 °C. Freezing storage was applied after RF heating to reduce the survival populations of both Salmonella and surrogate.